Podocyte loss involves MDM2‐driven mitotic catastrophe. Issue 3 (7th June 2013) - Mulay, Shrikant R; Thomasova, Dana; Ryu, Mi; Kulkarni, Onkar P; Migliorini, Adriana; Bruns, Hauke; Gröbmayr, Regina; Lazzeri, Elena; Lasagni, Laura; Liapis, Helen; Romagnani, Paola; Anders, Hans‐Joachim
Abstract: Podocyte apoptosis as a pathway of podocyte loss is often suspected but rarely detected. To study podocyte apoptosis versus inflammatory forms of podocyte death in vivo, we targeted murine double minute (MDM)‐2 for three reasons. First, MDM2 inhibits p53‐dependent apoptosis; second, MDM2 facilitates NF‐κB signalling; and third, podocytes show strong MDM2 expression. We hypothesized that blocking MDM2 during glomerular injury may trigger p53‐mediated podocyte apoptosis, proteinuria, and glomerulosclerosis. Unexpectedly, MDM2 blockade in early adriamycin nephropathy of Balb/c mice had the opposite effect and reduced intra‐renal cytokine and chemokine expression, glomerular macrophage and T‐cell counts, and plasma creatinine and blood urea nitrogen levels. In cultured podocytes exposed to adriamycin, MDM2 blockade did not trigger podocyte death but induced G2/M arrest to prevent aberrant nuclear divisions and detachment of dying aneuploid podocytes, a feature of mitotic catastrophe in vitro and in vivo . Consistent with these observations, 12 of 164 consecutive human renal biopsies revealed features of podocyte mitotic catastrophe but only in glomerular disorders with proteinuria. Furthermore, delayed MDM2 blockade reduced plasma creatinine levels, blood urea nitrogen, tubular atrophy, interstitial leukocyte numbers, and cytokine expression as well as interstitial fibrosis. Together, MDM2‐mediated mitotic catastrophe is a previously unrecognized variant of podocyte loss where MDM2 forces podocytes to complete the cell cycle, which in the absence of cytokinesis leads to podocyte aneuploidy, mitotic catastrophe, and loss by detachment. MDM2 blockade with nutlin‐3a could be a novel therapeutic strategy to prevent renal inflammation, podocyte loss, glomerulosclerosis, proteinuria, and progressive kidney disease. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.